The Fishers of the Archipelago Sea - resilience, sustainability, knowledge and agency - Sonck-Rautio, Kirsi (fi=Turun yliopisto|en=University of Turku|, 2019)
This doctoral dissertation combines ethnology and environmental science in order to recognise changes in the operational environment of the livelihoods and lifestyles of coastal small-scale fishers in the Archipelago Sea and the constraints that mostly influence the abundance and resilience of fisheries in the Archipelago Sea — from the fishers’ perspective. This study focuses on recognising the mechanisms that are decreasing resilience as well as examining the relationships between policy-making, scientific research and knowledge by applying the framework of political ecology. Finally, the aim is to find solutions for promoting transformations that will foster cultural resilience and sustainability as well as other dimensions of both. The research material for the doctoral dissertation was gathered by conducting ethnographic fieldwork, including 23 in-depth interviews and participant observa¬tion. Media and scientific articles and reports also formed a portion of the material analysed for this study. The research material was analysed abductively, and as a practical tool, qualitative analysis software Nvivo was applied as well. The timeframe of the analysis is from 1880 to the present, starting from the commercialisation of winter-seining in the Archipelago Sea and concluding with a discussion of the pres¬ent-day challenges facing fisheries. There is, however, an embedded future-oriented thinking present throughout this study, as many of the concepts applied, such as resilience and adaptation, contain an implicit future-thinking aspect. It was found that according to fishers, the most important constraint influencing the resilience of small-scale fisheries is the ever-increasing number of environmental policies and an unwillingness to acknowledge the local ecological knowledge pos¬sessed by the fishers. The ensuing environmental conflict is to some extent a con¬sequence of not including the dimension of cultural sustainability in policy-making processes, or in research involving environmental management and conservation, and not recognising the potential offered by local ecological knowledge both for pro¬moting overall sustainability and also as a tool for enhancing the social acceptance of environmental policies.

Tämä tutkimus yhdistää kansatiedettä ja ympäristötieteitä tutkiessaan kalastajien näkökulmasta pienimuotoisen rannikkokalastuksen toimintympäristössä tapahtuneita muutoksia, sekä niitä tekijöitä, jotka haittaavat kalastuselinkeinon hyvinvointia ja joustavuuttaa Saaristomeren rannikkoalueilla. Tutkimuksessa tunnistetaan poliittisen ekologian tarjoaman teoreettisen viitekehyksen avulla niitä mekanismeja, jotka heikentävät kalastusyhteisöjen sopeutumiskykyä ja joustavuutta, sekä perehdytään päätöksenteon, tieteen ja erilaisten tiedon lajien välisiin suhteisiin. Lopulta tavoitteena on löytää ratkaisuja siihen, kuinka kalastuselinkeinossa tapahtuvat muutokset voisivat tukea muiden kestävyyden ja joustavuuden ulottuvuuksien lisäksi myös kulttuurista joustavuutta ja kestävyyttä. Tutkimusaineisto on kerätty etnografisin menetelmin, mukaanlukien osallistuvaa havainnointia sekä 23 syvähaastattelua. Mediamateriaali ja tieteelliset artikkelit sekä raportit muodostivat myös osan tutkimusaineistosta. Aineisto analysoitiin abduktiivisesti, käyttäen praktisena työkaluna laadullisen aineiston analyysiohjelmisto Nvivoa. Tutkimus ajoittuu 1880-luvulta, jolloin Saaristomeren nuottakalastus lähti kaupallistumaan, nykypäivään. Tutkimuksessa on kuitenkin myös tulevaisuuteen suuntaava ote, sillä monet tutkimukselle tärkeät käsitteet, kuten sopeutuminen ja joustavuus, pitävät sisällään tulevaisuusorientoituneen näkökulman. Tutkimuksessa todettiin, että kalastajien näkökulmasta suurin haaste pienimuotoisen rannikkokalastuksen sopeutumiskyvylle ja joustavuudelle on jatkuvasti kiristyvä ulkopuolelta tuleva ympäristönhallinta, sekä päätöksentekoon liittyvien prosessien aikana huomiotta jätetty kalastajien paikallinen ekologinen tieto. Vallalla oleva ympäristökonflikti Saaristomeren alueella on jossain määrin seurausta siitä, ettei kulttuurisen kestävyyden ulottuvuutta ole huomioitu ympäristöön ja luonnonsuojeluun liittyvässä päätöksenteossa, tai tieteellisessä tutkimuksessa. Paikallinen ekologinen tieto voisi edesauttaa kokonaisvaltaisen kestävän kehityksen toteutumista, sekä osaltaan lisätä ympäristönhallintaan liittyvien päätösten paikallista hyväksyntää, mutta tämän potentiaalin hyödyntämättä jättäminen osaltaan syventää käynnissä olevaa ympäristökonfliktia.